Spectrophotometric Determination of Adefovir Dipivoxil in bulk and Pharmaceutical Formulation - Zaheer Ahmed; Y. N. Manohara; K. P. Channabasawaraj; Manish Majumdar (E-Journal of Chemistry)
Two selective and sensitive spectrophotometric methods have been developed for the estimation of adefovir dipivoxil in bulk and pharmaceutical preparations. Adefovir dipivoxil was subjected to acid hydrolysis and the hydrolysed product used for the estimation. The methods are based on the reaction with 3-methyl-2-benzothiazolinone hydrazone in the presence of ferric chloride, to form a colored species with absorption maxima at 627 nm. The second method is based on the reaction of drug with 1,2 naphthaquinone -4-sulphonic acid sodium salt, under alkaline conditions which absorbs maximally at 454 nm. Beers law is obeyed in the concentration range of 5-25 µg/mL and 2-10 µg/mL respectively. These methods were extended to pharmaceutical formulations and there was no interference from excepients and diluents. The analytical parameters were evaluated.